miR-379-5p affects breast cancer cell behavior by targeting UBE2E3 ubiquitin conjugating enzyme. - Araya K Schroder; Conor J Loy; Fernanda Aiala; Jazmyn Rafique; Arnob Ghosh; Lina I Yoo (PLoS ONE)
MicroRNAs (miRNAs) play an increasingly recognized role in modulating cancer development. Due to their function in regulating gene expression, miRNAs can suppress or promote tumorigenesis. miR-379-5p expression is downregulated in multiple human cancers, including breast and bladder cancers. However, the mRNAs targeted by miR-379-5p that promote cancer development have not been fully identified. Our goal was to identify a gene whose expression is regulated by miR-379-5p, and which may contribute to cancer development in cells where miR-379-5p expression is reduced. Bioinformatics analysis showed the UBE2E3 ubiquitin conjugating enzyme gene to be a potential target for miR-379-5p. To verify that UBE2E3 is a target, we transfected normal human epithelial mammary cells and breast adenocarcinoma cell lines with a miR-379-5p mimic. The mimic reduced UBE2E3 mRNA and protein levels, as would be predicted for a miR-379-5p target. To determine if UBE2E3 is a direct target of miR-379-5p, we engineered two luciferase reporter gene constructs to contain either a wild-type putative miR-379-5p binding sequence isolated from the 3'UTR of the UBE2E3 gene, or a scrambled sequence. The luciferase assay showed that the miR-379-5p mimic suppressed luciferase activity for the WT binding sequence reporter, but not for the scrambled reporter, showing that the effect of miR-379-5p on UBE2E3 expression is likely to be direct. Finally, to determine if the effect of miR-379-5p on UBE2E3 is related to cellular behaviors that play a role in cancer development, we measured cell viability by resazurin assay, cell proliferation by BrdU assay, and apoptosis by caspase 3/7 activation assay. The miR-379-5p mimic and silencing UBE2E3 expression both resulted in significantly diminished cell viability, while silencing UBE2E3 demonstrated both higher proliferation and apoptotic rates. Overall, these results suggest that while the overall effect of miR-379-5p is to inhibit breast cell viability and proliferation, the effect of silencing its target UBE2E3 is more complex because it induces both cell proliferation and apoptosis.